THE ASSESSMENT OF KNOWLEDGE AND ATTITUDE OF THE NURSES TOWARDS PALLIATIVE CARE - ASLAM , J; SADDIQUE , H; TASNEEM , SS; JABEEN , R (Biological and Clinical Sciences Research Journal, 2024)
Palliative care aims to improve the quality of life for patients with life-limiting illnesses by addressing physical, psychological, and spiritual needs. Nurses play a pivotal role in providing palliative care, yet their knowledge and attitudes significantly influence its quality Objective: To assess the knowledge and attitudes of nurses toward palliative care in a tertiary care hospital in Lahore, Pakistan. Methods: A descriptive cross-sectional study was conducted among 131 nurses using a structured and validated questionnaire. Data were analyzed using SPSS version 26, with results presented as frequencies and percentages. Results: The study revealed that 48.2% of nurses demonstrated moderate knowledge of palliative care, while 38.9% had low knowledge levels. Most participants (68.7%) exhibited neutral attitudes, with only 21.4% displaying positive attitudes. Nurses with higher qualifications and more clinical experience had better knowledge and attitudes compared to their counterparts. Conclusion: The findings highlight significant gaps in nurses’ knowledge and attitudes toward palliative care, emphasizing the need for targeted educational interventions and training programs. Integrating palliative care into nursing curricula and providing institutional support can improve the delivery of holistic, patient-centered care in Pakistan.